REGULADOR DE CRESCIMENTO E MODOS DE CONTROLE DE PLANTAS DANINHAS EM HÍBRIDOS DE MILHO - Ferreira, Camila (2012)
Increase the productive potential of agricultural crops with cultivation practices and management are some challenges of agricultural research in the face of growing demand for food. Accordingly, experiments were conducted with the aim to evaluate the effects of the growth regulator trinexapac-ethyl combined or not with modes of application of herbicides in corn. There were two distinct works, one evaluating the effects of trinexapac-ethyl at different doses and application times and another evaluating the consequences of desiccation or not the area in pre-seeding and application of methods of herbicides post-emergence combined or not the growth regulator, in two corn hybrids. In the season 2010/11 were carried out two experiments, one with the hybrid Status TL and the other with the Maximus TLTG,both in the experimental design of randomized blocks in factorial scheme 4 x 4 (trinexapac-ethyl applied at stages V2, V4, V6 and V8 corn, at doses of 0.0, 187.5, 375.0 and 562.5 g ha-1). The results showed that the time of application did not affect the morphological characteristics of both hybrids, at the dose of the regulator, to the Status TL no material effect on the measured characteristics, but for the Maximus TLTG, increasing the dose of the product resulted in an increased width and decrease in length of the sheet above the ear, with no effect on components of production and productivity. In the season 2010/11 and 2011/12, there were two experiments in each year, in a randomized block design in a factorial 2 x 2 x 2, with treatments consisting of desiccation or not the day of seeding, the unique application sequential or post-emergence herbicides, in combination with atrazine and mesotrione for hybrid Status TL and glyphosate to Maximus TLTG, besides the application or not a growth regulator, trinexapac-ethyl in combination with postemergence herbicides. Desiccation in two seasons on the day of seeding resulted in greater productivity for the Maximus TLTG. The productivity of Status TL increased with desiccation in pre-sowing only in 2010/11 crop. The mode of application of herbicides post-emergence changed some yield components of hybrid Status TL in 2010/11 crop. The application of trinexapac-ethyl did not affect substantially the characteristics of the hybrids in two seasons.